O degradacji pedagogiki i konieczności sięgania do źródeł. Na marginesie ostatniego seminarium – kolokwium toruńskie - Rudnicki, Zbigniew; Futyma, Sławomir (Studia Edukacyjne, 2020)
In 2019, one of the publishing houses published a book by Professor Aleksander Nalaskowski entitled: Kwieciński The Last Thursday Seminar. This publication is a record of a conversation between two important representatives of Polish science. It can become an inspiration for a change in Polish pedagogy. Professors Aleksander Nalaskowski and Zbigniew Kwieciński formulate a diagnosis of its current state and indicate new directions of development of this socially important scientific discipline. Interesting for the future functioning of this discipline seems to be the foundation of decency and quot; love and quot; understood as unconditional kindness, which is a constitutive feature of humanity.